Biological properties of selected Amaranthaceae halophytic species: A review - Marija Todorović; Nenad Zlatić; Biljana Bojović; Milica Kanjevac (Universidade de São Paulo, 2023)
Abstract The family Amaranthaceae contains a large number of halophytic species. The aim of this paper is to present a review of biologically significant halophytes in the flora of Serbia belonging to this family. This review includes a description of the following 18 species: Atriplex littoralis L., A. rosea L., A. halimus L., Bassia sedoides Pall., B. scoparia (L.) A.J.Scott., B. prostrata (L.) Beck., Beta trigyna W. et K., Camphorosma annua Pall., C. monspeliaca L., Chenopodium ambrosioides L., Ch. polyspermum L., Ch. vulvaria L., Ch. hybridum L., Ch. album L., Ch. rubrum L., Salicornia europaea L., Suaeda maritima (L.) Dum., Salsola soda L. These species are sources of biologically active substances and have a good potential for multi-purpose applications. Most extracts of these species have been found to exhibit biological activities such as antioxidant, anticancer, antibacterial, antifungal, antiinflammatory and others. The aim of this review is to describe these species including their morphology, distribution, phytochemistry, as well as their use for medicinal and food purposes.